Implementation of Interprofessional Collaboration in Patients Care: A Literature Review - Irawaty Djaharuddin; Irwin Aras; Rina Masadah; Irawan Yusuf; Andriany Qanitha (Physical Activity, Nutrition and Health Sciences Journal, 2025)
Interprofessional collaboration (IPC) in healthcare is a dynamic process where healthcare professionals from different disciplines work together to provide patient-centered care. The primary goal of IPC is to improve patient outcomes through coordinated, comprehensive care that addresses the physical, emotional, and social needs of patients. Effective IPC requires effective communication, mutual respect, and a shared understanding of roles and responsibilities among the team members. A collaborative team approach enables healthcare professionals to leverage their unique expertise to make informed decisions that enhance patient care, reduce healthcare costs, and increase patient satisfaction. The benefits of IPC implementation are improved patient safety, increased job satisfaction for healthcare professionals, and enhanced healthcare outcomes. Barriers to IPC include cultural differences, hierarchical structures, lack of communication, and inadequate training. To overcome these barriers, healthcare organizations need to invest in education, training, and support for IPC. Overall, IPC is a vital component of high-quality patient care, and it requires ongoing commitment and effort from all members of the healthcare team.